Pelaksanaan Akta 172 dan 171 dalam pembangunan fizikal oleh Pihak Berkuasa Tempatan - Mohamad Rizal, Mohamad Radzi (2014)
Local governments also known as the Local Authority (LA) is the government in the third and final stage in the administrative machinery of the country. It is set to be an intermediary or coordinator between the Federal, State and Local Authorities (LA) in matters relating to the government. Local government also plays a role in the allocation of the State Government or the Federal Government for the 11 Local Authorities in the state of Kedah to undertake a public facility projects that have been identified based on the laws and policies of government agencies and subject to 3 of the master of the Local Government Act (Act 171), Town and Country Planning Act (Act 172) and the Street, Drainage and Building (Act 133). Particular incident, the project paper to see how the implementation of the act in the physical development of economic influence in Kedah Darul Aman Project Paper also aims to find out the problems faced by the Local Authority (LA) and its role in the performance of duties associated with the government and also to identify the recommendations to strengthen the strategy of Local Authorities (LA) in improving physical economy in Kedah Darul Aman in particular. Data collection was conducted using a set of questionnaire and a total of 15 respondents participated in this study and data analysed using descriptive method of analysis. Results showed that the act is important in matters relating to the Local Authority (LA) to perform a public facility projects that are based on the Law and Government Policies related to it in accordance with the Philosophy and Vision 2020. The proposed study identified to enhance and strengthen its strategy of Local Authority (LA) is to increase the total allocation from the Ministry of Housing and Local Government (ministry) and other Federal agencies. The addition of staff, especially technical personnel to improve the performance of tax collection, license, fines, compound, and the arrears within the stipulated time and to study the privatization programs involving the role and functions of the Local Authority (LA) itself.